The Dynamics of Religious Conflict and Social Movements: An Islamic Economic Perspective - Baihaqi Baihaqi (Fakultas Syariah IAIN Langsa, 2026)
Ideally, religion in the perspective of Islamic economics functions as a unifying instrument that upholds distributive justice, social welfare, and harmony among groups. However, in reality, religion is often instrumentalized in social conflicts rooted in structural economic inequality, thereby triggering fragmentation and identity-based mobilization. This study aims to analyze the dynamics of religious conflict and social movements, as well as to examine the role of Islamic economics as a solution in reducing such conflicts. This article is categorized as field research with a qualitative approach, and the methodology used is an empirical legal study. The findings conclude that conflicts that appear to be religious in nature are essentially driven by unjust resource distribution, while religion-based social movements emerge as a response to economic marginalization. Islamic economics has the potential to serve as an instrument of social engineering through the optimization of zakat, waqf, and inclusive economic systems; however, its implementation remains suboptimal. Therefore, a transformation toward a more universal and interfaith collaborative economic approach is needed, along with inclusive public policy support, so that religion can function as social capital in creating stability and societal welfare.